2020
DOI: 10.1038/s41467-020-14570-z
|View full text |Cite|
|
Sign up to set email alerts
|

Bacterial adaptation is constrained in complex communities

Abstract: A major unresolved question is how bacteria living in complex communities respond to environmental changes. In communities, biotic interactions may either facilitate or constrain evolution depending on whether the interactions expand or contract the range of ecological opportunities. A fundamental challenge is to understand how the surrounding biotic community modifies evolutionary trajectories as species adapt to novel environmental conditions. Here we show that community context can dramatically alter evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
109
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 51 publications
11
109
0
Order By: Relevance
“…Moreover, transcriptome analysis of the endophyte Bacillus mycoides EC18 showed that an upregulation of genes involved in amino acids metabolism, transcriptional regulators, and signal transduction can play an important role in the adaptation of endophytic strains to their ecological niche (Yi et al, 2017). Scheuerl et al (2020) addressed also the question on how the surrounding bacterial community affects evolutionary trajectories of strain adaptation to new niches by studying environmental samples in artificial micro-ecosystems. They found that the diversity of surrounding bacterial communities as well as characteristics of the strain such as genome size are important factors for strain adaptation to new environmental conditions (Scheuerl et al, 2020).…”
Section: Adaptation Of Strains To Environmental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, transcriptome analysis of the endophyte Bacillus mycoides EC18 showed that an upregulation of genes involved in amino acids metabolism, transcriptional regulators, and signal transduction can play an important role in the adaptation of endophytic strains to their ecological niche (Yi et al, 2017). Scheuerl et al (2020) addressed also the question on how the surrounding bacterial community affects evolutionary trajectories of strain adaptation to new niches by studying environmental samples in artificial micro-ecosystems. They found that the diversity of surrounding bacterial communities as well as characteristics of the strain such as genome size are important factors for strain adaptation to new environmental conditions (Scheuerl et al, 2020).…”
Section: Adaptation Of Strains To Environmental Conditionsmentioning
confidence: 99%
“…Scheuerl et al (2020) addressed also the question on how the surrounding bacterial community affects evolutionary trajectories of strain adaptation to new niches by studying environmental samples in artificial micro-ecosystems. They found that the diversity of surrounding bacterial communities as well as characteristics of the strain such as genome size are important factors for strain adaptation to new environmental conditions (Scheuerl et al, 2020). Although this study addressed environmental microorganisms (and not specifically endophytes), this kind of experimental evolutionary approach can help to better understand the required traits for successful penetration and internal plant colonization by endophytes.…”
Section: Adaptation Of Strains To Environmental Conditionsmentioning
confidence: 99%
“…Several studies have focused on genome signatures variations (GC, tetranucleotide signatures, codon usage, purine-pyrimidine ratio) associated with different environments (reviewed in Dutta and Paul (2012) 12 ). Others, have studied bacterial adaptation to shifting environments 13 , or have targeted a specific evolutionary process across several lifestyles (homologous recombination 14 , selection 15 , etc.). Most of these studies, however, considered different species living in different environments, or closely related species with a different lifestyle (i.e.…”
mentioning
confidence: 99%
“…However, it must be re-emphasized that the protective strains studied herein were evolved in the absence of a complex microbial community with the animal host. The community context can alter the evolutionary outcomes of individual microbe species [40,41]. Future research could test whether microbe-mediated protection can be enhanced via evolution in hosts with a resident microbiota.…”
Section: Discussionmentioning
confidence: 99%